2017
DOI: 10.1038/s41529-017-0020-3
|View full text |Cite
|
Sign up to set email alerts
|

The controlling role of sodium and carbonate on the atmospheric corrosion rate of aluminum

Abstract: Aluminum and aluminum alloys are widely used in many outdoor applications due to their inherent corrosion resistance attributed to the formation of a protective oxide layer. While corrosion rates are generally considered low for aluminum in many atmospheric environments, understanding of the corrosion performance over time is necessary to predict the cost, safety, and esthetics of these materials. The vast majority of the knowledgebase of atmospheric aluminum corrosion is built on environment-response relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…The trend in cumulative volume loss observed in Fig. 1 is consistent with previous studies of Al under fixed salt load and constant humidity conditions: after some period of initial corrosion upon humidity exposure 22,23 , measurable loss effectively ceases. This occurred after similar exposure times (100-500 h) in both this study and in those of refs.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The trend in cumulative volume loss observed in Fig. 1 is consistent with previous studies of Al under fixed salt load and constant humidity conditions: after some period of initial corrosion upon humidity exposure 22,23 , measurable loss effectively ceases. This occurred after similar exposure times (100-500 h) in both this study and in those of refs.…”
Section: Discussionsupporting
confidence: 90%
“…Schaller et al found the time at which corrosion stifled strongly correlated with observed dry-up of electrolyte for NaCl droplets on AA1100 at 98% RH 23 . This was attributed to corrosion stifling by a reaction of the cathode electrolyte with atmospheric CO 2 during corrosion which precipitated sodium aluminum carbonate compounds that dry the surface 23,24 .…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations